Antitumor Activity of Tubulin-Binding Agent MPC-6827 on Different Types of Cancer Cell Lines: Antitumor Activity of MPC-6827 - Topçul, Mehmet R.; Çetin, İdil (Cellular and Molecular Biology, 2022)
In this study, the antitumor effects of tubulin-binding agent MPC-6827 on HeLa, MCF-7 and A549 cell lines originated from cervix carcinoma, metastatic breast adenocarcinoma and adenocarcinomic human alveolar basal epithelial cells respectively were determined. Cell index, BrdU labelling index, mitotic index and apoptotic index were evaluated in experiments. In cell index experiment 2 nM, 4 nM, 6 nM, 8 nM, 10 nM MPC-6827 applied to three cell lines. These parameters showed that 4 nM was the optimum concentration for HeLa and A549 cells, while 2 nM was the optimum concentration for MCF-7 cells. The use of optimum concentrations for each cell line has shown that while there was a significant decrease in mitotic index, BrdU labelling index, there was a significant increase in apoptotic index.